Delays in Construction Project : A Review - Kamandang, Zetta Rasullia; Casita, Cintantya Budi (Institut Teknologi Sepuluh Nopember, 2018)
Delays in construction projects schedule is one of the most noticed problems. Delays may be caused by several project parties and further categorized into excusable non-compensable delays (EN) caused by many factors beyond parties’ control, excusable-compensable delays (EC) caused by the owner, and non-compensable delays (NE) caused by the contractor. Another issue is concurrency in delays. The result of concurrent delay often leads the project parties into complicated situations. Thus, understanding the causes and identifying the types of delays are essential to be done before executing the delay analysis methods in order to allocating the liability of each party. This study concludes that some existed schedule delay analysis methods produce different results, therefore, the practitioners or schedule delay analyst should understand the anticipated results that can be accepted by all construction projects parties.